How do you find the derivative of #x=((s-1)(s-2))/(s-3)#?
By signing up, you agree to our Terms of Service and Privacy Policy
To find the derivative of (x = \frac{{(s - 1)(s - 2)}}{{s - 3}}), you can use the quotient rule. The quotient rule states that if you have a function of the form (f(x) = \frac{{g(x)}}{{h(x)}}), then its derivative is given by [f'(x) = \frac{{g'(x)h(x) - g(x)h'(x)}}{{[h(x)]^2}}.]
Applying the quotient rule to the given function (x = \frac{{(s - 1)(s - 2)}}{{s - 3}}), where (g(s) = (s - 1)(s - 2)) and (h(s) = s - 3), we get:
[x' = \frac{{(s - 1)(s - 2)'(s - 3) - (s - 1)(s - 2)(s - 3)'}}{{(s - 3)^2}}.]
Now, differentiate (g(s) = (s - 1)(s - 2)) and (h(s) = s - 3), which gives:
[(s - 1)(s - 2)' = (1)(s - 2) + (s - 1)(1) = s - 2 + s - 1 = 2s - 3,]
and [(s - 3)' = 1.]
Substitute these derivatives back into the quotient rule formula:
[x' = \frac{{(2s - 3)(s - 3) - (s - 1)(s - 2)}}{{(s - 3)^2}}.]
Now, expand and simplify:
[x' = \frac{{2s^2 - 6s - 3s + 9 - (s^2 - 3s - 2s + 6)}}{{(s - 3)^2}}.]
[x' = \frac{{2s^2 - 9s + 9 - s^2 + 5s - 6}}{{(s - 3)^2}}.]
[x' = \frac{{s^2 - 4s + 3}}{{(s - 3)^2}}.]
So, the derivative of (x = \frac{{(s - 1)(s - 2)}}{{s - 3}}) with respect to (s) is (x' = \frac{{s^2 - 4s + 3}}{{(s - 3)^2}}).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the derivative of #sin(x+y)=xy#?
- How do you find the derivative of the function #y=3x(6x-5x^2)#?
- How do you find the derivative of #(x+4)/x#?
- How do you find #dy/dx# by implicit differentiation of #tan(x+y)=x# and evaluate at point (0,0)?
- How do you differentiate #f(x) =(2+x )( 2-3x)# using the product rule?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7